Oxidation and interdiffusion behavior of NiAlY/AlCrTaTiZr coating on Fe–Cr alloy prepared by magnetron sputtering - Yuanmi Zhang; Meifeng Li; Junpin Lin; Chungen Zhou (Journal of Materials Research and Technology)
An AlCrTaTiZr high-entropy alloy (HEA) as a diffusion barrier was prepared by sputtering to suppress interdiffusion across the NiAlY/Fe–Cr alloy interface. The oxidation and interdiffusion behavior of NiAlY coatings with and without the HEA diffusion barrier were investigated at 850 °C. The results indicate the oxidation mass gain of NiAlY and NiAlY/AlCrTaTiZr coatings were 0.45 and 0.39 mg cm−2 after 100 h, respectively. The thickness of the interdiffusion zone (IDZ) in the composite coating was thinner than that in the HEA-free layer. The HEA layer serves as an effective barrier against the interdiffusion between the NiAlY coating and the substrate, maintaining the high aluminium content in the coating and inhibiting the formation of brittle intermetallic phases in IDZ. Consequently, oxidation resistance of the composite coating is increased.